Investigation of Knowledge Management and Technology Absorption Attributes toward Technology Transfer Success in Automotive Industry - Siti Aishah, Md Hasan; Ahmad, Othman; Shariman, Mustafa (2009)
Knowledge Management (KM) and Technology Absorption (TA) have been a great issue of concern among researchers and companies for some time now and one of the factors that determine the success of technology transfer. Moreover, these areas contribute greatly to productivity and organization effectiveness as well as economic development. Hence, countries such as Malaysia concern very much for managing knowledge and adopting new technology as determining factors for technology transfer processes. Over the years, Malaysia has invested millions of ringgits to achieving knowledge transfer and is more involve in technology transfer especially the adoption of new technology. This paper will explore the potential attributes of knowledge management and technology absorption and how these attributes will determine the technology transfer successfulness in the automotive industry in Malaysia.